Uji perbandingan efektivitas ekstrak daun kemangi (Ocimum sanctum ) dan daun mint (Mentha arvensis) sebagai insektisida larva nyamuk Aedes aegypti - Ali Napiah Nasution; Mahwina Yusari Harahap; Erika Auria Sinaga; Salsabila Bizlany Harahap (Journal of Pharmaceutical and Sciences, 2023)
Mosquitoes are vectors of various parasitic and viral diseases, especially in tropical and subtropical regions. A mosquito is a type of small insect that belongs to the family Culicidae. They are known for their annoying nature and bite humans as well as other animals to obtain blood as a food source. Female mosquitoes need protein contained in the blood to develop and lay their eggs. This study is a laboratory experiment, with a true experimental post-test only control group design which aims to compare the effectiveness of basil leaf extract ocimum sanctum. and mint leaves of mentha arvensis. As an insecticide of mosquito larvae Aedes Aegepty. At a concentration of 5% basil extract of dead larvae is 40% and mint leaf extract is 24% of dead larvae. At a concentration of 10%, mint extract of dead larvae 32%, while basil leaf extract 56% of dead larvae. At a concentration of 15% mint leaf extract of larvae that died 60% while basil leaf extract 60% of larvae died, and at a concentration of 25% mint leaf extract of larvae that died 64% while basil leaf extract 72% of larvae died. The results showed that basil leaf extract was more effective as an insecticide for Aedes aegpyti mosquito larvae than basil leaf extract. The higher the concentration of mint leaf extarak and basil leaf extract, the higher it is effective as an insecticide of Aedes aegpyti mosquito larvae.